The efficacy and safety of auricular acupoint therapy on treating functional dyspepsia with insomnia: study protocol for a randomized controlled trial - Shen, Meng-Yuan; Lou, Qin-Yi; Liu, Shan; Li, Ze-Jiong; Lin, Tian-Chen; Zhou, Rong; Feng, Dan-Dan; Yang, Dong-Dong; Wu, Jian-Nong (Frontiers in Medicine, 2025)
BackgroundFunctional dyspepsia (FD) is a prevalent health issue currently lacking optimal treatment options, with its global incidence rate increasing in recent years. Clinical studies have recently focused on the application of auriculotherapy in functional gastrointestinal disorders that are accompanied by negative emotions. However, few randomized controlled trials have investigated the use of auriculotherapy for FD patients with insomnia, leaving the therapeutic efficacy and safety largely undefined. This study aims to evaluate the clinical efficacy and safety of auriculotherapy in treating FD patients with insomnia.Methods and analysisThis study is a single-center, randomized controlled clinical trial involving 80 patients with FD and insomnia. Using a central randomization system, the subjects are randomly assigned to the auricular acupressure group or the sham auricular acupressure group at a 1:1 ratio, with the auricular acupressure group targeting the concha region and the sham auricular acupressure group targeting the earlobe region. The primary outcome is the response rate at 2 weeks, and the secondary outcomes include the response rate at 8 weeks, sleep data assessed by actigraphy, modified Functional Dyspepsia Symptom Diary, short form-Nepean Dyspepsia Index, Self-rated Anxiety Scale, Self-rated Depression Scale, High Arousal Scale, and Heart Rate Variability. Efficacy results will be evaluated at baseline and at 2 and 8 weeks after treatment. Adverse events will be monitored throughout the study observation period.DiscussionThe results of this trial are anticipated to validate the efficacy and safety of auriculotherapy in improving symptoms of FD and insomnia, as well as in reducing negative emotional states.Clinical trial registrationClinicalTrials.gov, NCT06466044. Registered 14th May 2024, https://register.clinicaltrials.gov.